2015
DOI: 10.1038/mtna.2015.28
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Human Artificial Chromosome for Delivering Trophic Factors in a Rodent Model of Amyotrophic Lateral Sclerosis

Abstract: A human artificial chromosome (HAC) is maintained as an episome within a cell and avoids random integration into the host genome. It can transfer multiple and/or large transgenes along with their regulatory elements thereby resembling native chromosomes. Using this HAC system, we established mesenchymal stem cells (MSCs) that simultaneously expressed hepatocyte growth factor, glial cell line-derived neurotrophic factor, and insulin-like growth factor 1, termed HAC-MSCs. This cell line provides an opportunity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Intrathecal delivery of Riluzole has been investigated in both Gottingen minipigs and canine models [52,53] with both studies demonstrating higher Riluzole levels in the CNS while limiting the systemic dose that may lead to off-target side-effects. Additionally, gene therapy and therapies involving trophic factors to stimulate dying neurons [54,55] have shown promise in rodent models. Other animal studies have also shown that human stem cells administered intrathecally delay the onset of symptoms and prolong survival in ALS transgenic mice [56].…”
Section: Potential Implications For Intrathecal Als Therapeuticsmentioning
confidence: 99%
“…Intrathecal delivery of Riluzole has been investigated in both Gottingen minipigs and canine models [52,53] with both studies demonstrating higher Riluzole levels in the CNS while limiting the systemic dose that may lead to off-target side-effects. Additionally, gene therapy and therapies involving trophic factors to stimulate dying neurons [54,55] have shown promise in rodent models. Other animal studies have also shown that human stem cells administered intrathecally delay the onset of symptoms and prolong survival in ALS transgenic mice [56].…”
Section: Potential Implications For Intrathecal Als Therapeuticsmentioning
confidence: 99%
“… Human artificial chromosome (HAC). ( a ) Diagram of the alphoid tetO -HAC 37 ( tetO -HAC) used in this study. The HAC contains a unique gene-loading loxP site.…”
Section: Figurementioning
confidence: 99%
“… 40 The HAC consists of ~6,000 copies of the 42-bp tetracycline operator (tetO) sequence incorporated into every second alphoid DNA monomer of the 1.1 megabase-size alphoid DNA array. 37 , 43 The HAC has ~30 copies of the selectable marker blasticidin (bsr). ( b ) FISH of a donor hamster CHO cells and recipient human cell lines carrying the autonomously propagated HAC.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…4 Taking advantage of these features, MSC have been employed as tumoraccumulating cells for anticancer therapy in various mouse models. [5][6][7][8][9] Although several studies have combined human MSC and immunodeficient mice, few studies have developed models with mouse MSC and syngeneic mouse tumors. Syngeneic tumor models are critical for investigating in vivo antitumor T cell immunity after MSC therapy.…”
Section: Introductionmentioning
confidence: 99%